2009
DOI: 10.1097/qad.0b013e32831940a3
|View full text |Cite
|
Sign up to set email alerts
|

Delayed anti-HCV antibody response in HIV-positive men acutely infected with HCV

Abstract: Delayed seroconversion in HIV-positive individuals with acute HCV may result in delayed diagnosis and treatment. Where there is a clinical suspicion of recent HCV infection, for example, elevated alanine transaminase levels, HIV-infected patients should be screened for HCV RNA by RT-PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
140
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 15 publications
4
140
2
2
Order By: Relevance
“…15,16 Many factors have been found to influence the progression from low to high avidity. [23][24][25][26] A low avidity result with the assay described in this paper suggested that a recent HCV infection has occurred within ∼4-5 months. In this study, group 1 (acute patients) were defined as becoming anti-HCV positive after a previous negative result taken 4-6 months ago.…”
Section: Discussionmentioning
confidence: 75%
“…15,16 Many factors have been found to influence the progression from low to high avidity. [23][24][25][26] A low avidity result with the assay described in this paper suggested that a recent HCV infection has occurred within ∼4-5 months. In this study, group 1 (acute patients) were defined as becoming anti-HCV positive after a previous negative result taken 4-6 months ago.…”
Section: Discussionmentioning
confidence: 75%
“…Diagnosis of chronic infection is usually made on the basis of a positive anti-HCV anti body test [enzyme-linked immunosorbent assay (ELISA) AE recombinant immunoblot assay (RIBA)], confirmed by a positive HCV RNA [reverse transcriptase-polymerase chain reaction (RT-PCR)] test. However, a proportion of patients will have normal liver enzymes or a negative antibody test in the presence of chronic HCV viraemia [183][184][185][186][187].…”
Section: Diagnosis Of Hcv Infection In Hiv-infected Individualsmentioning
confidence: 99%
“…Over time, anti-HCV antibody levels decline such that it can be difficult to differentiate infection in the distant past from nonspecific false positivity [183][184][185][186][187].…”
Section: Diagnosis Of Hcv Infection In Hiv-infected Individualsmentioning
confidence: 99%
See 2 more Smart Citations